Path integral in quantum field theories - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: Starting from the Hamiltonian an alternative description of quantum mechanics has been given, based on the sum of all possible paths between an initial and a final point. Methods: Theoretical methods of mathematical physics. Integral method based on the path integral. Results: The method and concepts of the path integral could be applied to other branches of physics, not limited to quantum mechanics. Conclusions: The Path Integral approach gives a global description of fields, unlike the usual Lagrangian approach which is a local description of fields.